Wacana Pluralitas Agama dalam Islam: Kajian Hadis Ahkam terhadap Makna dan Cakupan Ahl al-Kitab dalam Tafsir M. Ghalib - Rif’ah, Andi Muh. Afwaz Fafaza; Abubakar, Achmad; Irham, Muhammad (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2026)
This study examines the concept of Ahl al-Kitab through the exegetical framework of M. Ghalib, focusing on the meaning, scope, and jurisprudential implications derived from legal hadiths (hadith ahkam) in his Qur'anic interpretation. Employing a qualitative approach through library research, this study analyzes M. Ghalib's exegetical methodology and situates his views within the broader discourse of classical and contemporary Islamic scholarship. The findings reveal that M. Ghalib's exegesis acknowledges Ahl al-Kitab as adherents of divinely revealed religions while distinguishing between those who maintain peaceful coexistence and those who adopt a hostile stance toward Muslims. On jurisprudential matters, his interpretive framework addresses three principal issues: first, the permissibility of consuming food slaughtered by Ahl al-Kitab, which M. Ghalib allows under specific conditions consistent with the majority scholarly position; second, the marriage of Muslim men with Ahl al-Kitab women, which he permits with certain qualifications, contrasting with the Indonesian Ulema Council (MUI) fatwa prohibiting such unions on grounds of maslahah; and third, the issues of greeting (salam) and social guardianship (walayah), which he treats as contextual rather than absolute prohibitions. Overall, M. Ghalib's exegesis reflects a hermeneutical orientation that balances theological integrity with openness toward religious plurality, grounded in the Qur'anic principles of tolerance and social justice. This study contributes to the contemporary discourse on Islamic legal pluralism and offers practical insights for religious scholars, educators, and policymakers engaged in fostering interfaith harmony within the pluralistic context of Indonesia.